2D In2S3 Nanoflake Coupled with Graphene toward High‐Sensitivity and Fast‐Response Bulk‐Silicon Schottky Photodetector. Issue 47 (14th October 2019) - Lu, Jianting; Zheng, Zhaoqiang; Yao, Jiandong; Gao, Wei; Zhao, Yu; Xiao, Ye; Li, Jingbo
Abstract: Silicon‐based electronic devices, especially graphene/Si photodetectors (Gr/Si PDs), have triggered tremendous attention due to their simple structure and flexible integration of the Schottky junction. However, due to the relatively poor light–matter interaction and mobility of silicon, these Gr/Si PDs typically suffer an inevitable compromise between photoresponsivity and response speed. Herein, a novel strategy for coupling 2D In2 S3 with Gr/Si PDs is demonstrated. The introduction of the double‐heterojunction design not only strengthens the light absorption of graphene/Si but also combines the advantages of the photogating effect and photovoltaic effect, which suppresses the dark current, accelerates the separation of photogenerated carriers, and brings photoconductive gain. As a result, In2 S3 /graphene/Si devices present an ultrahigh photoresponsivity of 4.53 × 10 4 A W −1 and fast response speed less than 40 µs, simultaneously. These parameters are an order of magnitude higher than pristine Gr/Si PDs and among the best values compared with reported 2D materials/Si heterojunction PDs. Furthermore, the In2 S3 /graphene/Si PD expresses outstanding long‐term stability, with negligible performance degradation even after 1 month in air or 1000 cycles of operation. These findings highlight a simple and novel strategy for constructing high‐sensitivity and ultrafast Gr/Si PDs for further optoelectronic applications. Abstract : A novel strategy for coupling 2D In2 S3 with graphene/Si photodetectors is demonstrated. The introduction of a double‐heterojunction design not only strengthens the light absorption of graphene/Si but also combines the advantages of the photogating effect and photovoltaic effect, which suppresses the dark current, accelerates the separation of photogenerated carriers, and brings photoconductive gain.